Ekstraksi Kulit Buah Naga sebagai Pewarna Alami - Anna Susanti (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Synthetic dyes are increasingly widespread usage and soharmful to human health so that it needs to be increased by using of natural dyes which is safe. Natural dyes can be obtained from plant pigments which contained from both of leaves and rind. Dragon fruit skin is one of the natural pigment source. Its skin totaling 30-35% of the fruit is often simply thrown away as trash. Dragon fruit skin produces natural red color produced by pigment called anthocyanin which can be used as a substitute from synthetic dyes to natural dyes. This research aims to find the optimum conditions for extraction of dragon fruit skin. Extraction was carried out by using 80% ethanol solvent by using a variable ratio of the amount of material and solvent (1: 9 1:10 1:11 1:12 1:13), temperature (50◦C, 60◦C, 70◦C, 80◦ C) and time (1 hour, 2 hours, 3 hours, 4 hours, 5 hours). After that, do the analysis phase of the anthocyanin content. The results showed that the optimum conditions for extraction of the dye from the dragon fruit skin with 80% ethanol at a ratio F: S 1:11, extraction temperature 50 ◦C and for 3 hours resulted in anthocyanin concentration of 7.180 mg / L.